EFFECT OF DEBT TO EQUITY RATIO AND INCOME SMOOTHING OF EARNINGS MANAGEMENT IN BAKRIE LAND DEVELOPMENT, TBK. - Muhamad Syahwildan (Kusuma Negara Business School, 2020)
To perform earnings management, the company needs some analysis and ratio in the financial statements. Financial ratios can be used to Determine earnings calculations. In this research, we use the Debt to Equity Ratio and Income Smoothing to know how big influence of the ratio to earnings management at PT. Bakrieland Development. Tbk. Data collection techniques are to use secondary Data Obtained from the financial statements of PT. Bakrieland Development, Tbk in the period 2009 - 2016, the data is taken from the website www.idx.go.id. Debt to Equity Ratio and Income Smoothing are Independent Variables (X) while Profit Management is Dependent Variable (Y). Linear Regression is used to analyze research data.